2020
DOI: 10.1016/j.isci.2020.101231
|View full text |Cite|
|
Sign up to set email alerts
|

Unveiling Molecular Recognition of Sialoglycans by Human Siglec-10

Abstract: HIGHLIGHTSWe unveiled the molecular basis of sialoglycans recognition by Siglec-10The conformation of sialoglycans drives the interaction with the protein Siglec-10 is able to recognize and bind complex N-glycansOur outcomes may open the venue for the design and development of novel glycomimetics

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

6
3

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 62 publications
1
21
0
Order By: Relevance
“…The stability of φ and ψ dihedral angles of the glycosidic linkages in the free state was monitored during 100 ns Molecular Dynamic simulation in explicit solvent, carried out using the Amber18 package ( Case et al, 2018 ) (See also Methods and Figure S2 ). Differently from the Neu5Ac trisaccharide ( Di Carluccio et al., 2019 ; Forgione et al, 2020 ), that in solution explores different populations depending on the values of φ torsion angle (−60°/180°), the Neu5Gc glycan preferentially adopts a conformation with φ around −60° (see Table S3 ).…”
Section: Resultsmentioning
confidence: 99%
“…The stability of φ and ψ dihedral angles of the glycosidic linkages in the free state was monitored during 100 ns Molecular Dynamic simulation in explicit solvent, carried out using the Amber18 package ( Case et al, 2018 ) (See also Methods and Figure S2 ). Differently from the Neu5Ac trisaccharide ( Di Carluccio et al., 2019 ; Forgione et al, 2020 ), that in solution explores different populations depending on the values of φ torsion angle (−60°/180°), the Neu5Gc glycan preferentially adopts a conformation with φ around −60° (see Table S3 ).…”
Section: Resultsmentioning
confidence: 99%
“…The N-terminal V-set Ig domain in the Siglec family contains common structural determinants, such as a conserved arginine in the F strand, key residue for the formation of salt bridge with the carboxyl group of sialic acid. 22,35,36 As for the Siglec-like adhesins SLBR-H and SLBR-B, despite the proximity in the binding site of arginine residues (Arg340 SLBR-H and Arg484 SLBR-B ) to the sialic acid unit of the ligands, no similar ionic interactions with the carboxyl group of Neu5Ac were detected, but important hydrogen bonds were found with the glycerol moiety, in particular with O8 and O9 of Neu5Ac. Instead, the carboxylate group of Neu5Ac established interactions with the threonine residue of the ΦTRY motif (Thr339 SLBR-H and Thr483 SLBR-B ).…”
Section: Rsc Chemical Biology Accepted Manuscriptmentioning
confidence: 99%
“…In the free state (figure S4), an equilibrium of three different conformations around the Neu5Ac-α-(2,3)-Gal glycosidic linkage was detected (corresponding to φ -60°/60°/180°). 22,23 Conversely, NOE and binding data revealed that, upon accommodation of 3'-SLn into the SLBR-H binding site, a bioactive conformation, stable along the MD simulation of Please do not adjust margins Please do not adjust margins SLBR-H -3'-SLn complex, was preferentially selected (figure S6).…”
Section: Slbr-h Interaction With 3'-slnmentioning
confidence: 99%
“…Antibody-mediated blockade of the CD24–Siglec-10 interaction robustly augments the phagocytosis of CD24 + cancer cells by macrophages [ 80 ]. Forgione et al performed a structural study coupled with molecular modeling analysis and uncovered that Siglec-10 favors sialylated complex-type N-glycans on substrates for binding [ 81 ].…”
Section: N-glycosylation In Cancer Immunitymentioning
confidence: 99%